Dissecting the genetic overlap of smoking behaviors, lung cancer, and chronic obstructive pulmonary disease: A focus on nicotinic receptors and nicotine metabolizing enzyme. Issue 7 (16th August 2020) - Bray, Michael J.; Chen, Li‐Shiun; Fox, Louis; Hancock, Dana B.; Culverhouse, Robert C.; Hartz, Sarah M.; Johnson, Eric O.; Liu, Mengzhen; McKay, James D.; Saccone, Nancy L.; Hokanson, John E.; Vrieze, Scott I.; et al.
Abstract: Smoking is a major contributor to lung cancer and chronic obstructive pulmonary disease (COPD). Two of the strongest genetic associations of smoking‐related phenotypes are the chromosomal regions 15q25.1, encompassing the nicotinic acetylcholine receptor subunit genes CHRNA5‐CHRNA3‐CHRNB4, and 19q13.2, encompassing the nicotine metabolizing gene CYP2A6 . In this study, we examined genetic relations between cigarettes smoked per day, smoking cessation, lung cancer, and COPD. Data consisted of genome‐wide association study summary results. Genetic correlations were estimated using linkage disequilibrium score regression software. For each pair of outcomes, z‐score‐z‐score (ZZ) plots were generated. Overall, heavier smoking and decreased smoking cessation showed positive genetic associations with increased lung cancer and COPD risk. The chromosomal region 19q13.2, however, showed a different correlational pattern. For example, the effect allele‐C of the sentinel SNP (rs56113850) within CYP2A6 was associated with an increased risk of heavier smoking ( z ‐score = 19.2; p = 1.10 × 10 −81 ), lung cancer ( z ‐score = 8.91; p = 5.02 × 10 −19 ), and COPD ( z ‐score = 4.04; p = 5.40 × 10 −5 ). Surprisingly, this allele‐C (rs56113850) was associated with increased smoking cessation ( z ‐score = −8.17; p = 2.52 × 10 −26 ). This inverse relationship highlights the need for additional investigation to determine how CYP2A6 variation could increase smoking cessation while also increasing the risk of lung cancer and COPD likely through increased cigarettes smoked per day.